Pembinaan Manajemen Peserta Didik dalam Perspektif Pendidikan Islam - Maya Elok Kharisma; Fadillah Hadid; M. Alvin Faiz; Akram Fadhlurrahman (CV. Syntax Corporation Indonesia, 2021)
The purpose of this study is to discuss the development of student management in the perspective of Islamic education. The analytical methodology used in this study is a qualitative analysis based on an observational model to find out what school development is from the perspective of Islamic education. The results of this study indicate that Islamic education management consists of three words expressed by Rahendra Maya, namely the terms management, education and Islam. Revealed Islam includes the Qur'an and the Sunnah of the Prophet, and cultural Islam includes the expression of the companions of the Prophet, the understanding of the ulama, the understanding of the scholars and Muslim culture. Therefore, the discussion of Islamic education management always involves revelation and Islamic culture plus the rules of education management in general. The management of Islamic educational institutions is a realistic basis for formulating the principles of Islamic education management